Polymer Processing: Modeling and Correlations Finalized to Tailoring Plastic Part Morphology and Properties - Titomanlio, Giuseppe (Materials (Basel), 2019)
The analysis of polymer processing operations requires the description of simultaneous transient momentum and heat transfer down to material solidification. The aim of the analysis is to improve and, hopefully, optimize the final properties that are determined by the final morphology of the part. In this special issue, consisting of 1 review and 11 research articles detailing several polymer processing operations, experimental and numerical analyses have been conducted in order to identify and describe the main relevant phenomena, that affect the product morphologies and properties.